Kepemimpinan Kepala Sekolah Perempuan Lembaga Pendidikan Islam Dasar Di Kecamatan Nglegok Kabupaten Blitar - Badrus; Lilik Sri Wahyuni (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2019)
This study aims to: (1) describe the Leadership of Women's School Principals in Nglegok, Blitar Regency; (2) describing the factors that support and hinder the leadership of women school principals in Nglegok, Blitar Regency. This research is a qualitative research. The research sites are Islamic Elementary Echool â€œKreatif Zaid Bin Tsabitâ€, Primary School Ngoran 02, and Integrated Islamic Elementary School Wildan Mukholladun Nglegok Blitar. Resource persons for the study are principals, teachers, and operators. Data collection uses participant observation, interviews, and documentation. Data validity uses triangulation with data sources. Data analysis techniques by data reduction, data presentation, data analysis, drawing conclusions, and verification. The results showed: (1) Leadership of female school principals in Nglegok Sub-District, Blitar Regency had been going well, it was proven that the school principal had carried out several strategic policies. (2) Factors that support the leadership of female school principals in Nglegok District, Blitar Regency include government policies, technological advances, increased awareness of the potential and existence of women, state recognition of women's potential, human rights enforcement and a democratic system. While the inhibiting factors are rigidity in interpreting the text of religion, feelings of doubt and lack of confidence in some women.